The Experience of Individuals Transitioning from In-Center Hemodialysis to Home Dialysis After a Suboptimal Start: A Mixed-Method Study - Sauve, Caroline (Université d'Ottawa / University of Ottawa, 2015)
Background It is estimated that up to 50% of individuals begin dialysis with a suboptimal start. Objective To explore the transition to home dialysis, with a special emphasis on this transition after a suboptimal start. Methods A two-phased mixed methods study including: 1) a scoping review and meta-synthesis on the facilitators and barriers to home dialysis and 2) a qualitative study using thematic analysis on the transition to home dialysis after a suboptimal start. Findings 12 studies were included in the scoping review. Principle facilitators and barriers included Support, Burden of Care, and Disruption of Life. Six individuals were included into the qualitative phase. Through their interviews, they expressed the importance of the timely delivery of information, support, living with loss, managing fear, living with hope, and learning to live with dialysis. Conclusions The facilitators and barriers to home dialysis were similar in both studies suggesting that the transition to home dialysis is similar regardless of the nature of dialysis start. Several subthemes obtained from the qualitative study however revealed that a suboptimal dialysis start entails unique challenges, requiring the delivery of more support and education.
Keywords: Dialysis; Home Dialysis; Transition